Preexposure Prophylaxis for HIV Prevention in a Large Integrated Health Care System: Adherence, Renal Safety, and Discontinuation - Marcus, Julia L; Hurley, Leo B; Hare, Charles Bradley; Nguyen, Dong Phuong; Phengrasamy, Tony; Silverberg, Michael J; Stoltey, Juliet E; Volk, Jonathan E (Journal of acquired immune deficiency syndromes (1999), 2016)
Placebo-controlled and open-label studies have demonstrated the safety and efficacy of daily oral preexposure prophylaxis (PrEP) in preventing HIV infection, but data are limited on real-world PrEP use. We conducted a cohort study from July 2012 through June 2015 of Kaiser Permanente Northern California members initiating PrEP. We assessed pharmacy refill adherence and discontinuation, decreases in estimated glomerular filtration rate (eGFR), and sexually transmitted infection (STI)/HIV incidence. Overall, 972 individuals initiated PrEP, accumulating 850 person-years of PrEP use. Mean adherence was 92% overall. Black race/ethnicity [adjusted risk ratio (aRR) 3.0; 95% confidence interval: 1.7 to 5.1, P < 0.001], higher copayments (aRR 2.0; 1.2 to 3.3, P = 0.005), and smoking (aRR 1.6; 1.1 to 2.3, P = 0.025) were associated with <80% adherence. PrEP was discontinued by 219 (22.5%); female sex (aRR 2.6; 1.5 to 4.6, P < 0.001) and drug/alcohol abuse (aRR 1.8; 1.3 to 2.6, P = 0.002) were associated with discontinuation. Among 909 with follow-up creatinine testing, 141 (15.5%) had an eGFR <70 mL·min·1.73 m and 5 (0.6%) stopped PrEP because of low eGFR. Quarterly STI positivity was high and increased over time for rectal chlamydia (P < 0.001) and urethral gonorrhea (P = 0.012). No HIV seroconversions occurred during PrEP use; however, 2 occurred in individuals who discontinued PrEP after losing insurance coverage. PrEP adherence was high in clinical practice, consistent with the lack of HIV seroconversions during PrEP use. Discontinuation because of renal toxicity was rare. STI screening every 6 months, as recommended by current guidelines, may be inadequate. Strategies are needed to increase PrEP access during gaps in insurance coverage.